2016
DOI: 10.1002/2016gl071778
|View full text |Cite
|
Sign up to set email alerts
|

Monsoon circulations and tropical heterogeneous chlorine chemistry in the stratosphere

Abstract: Model simulations presented in this paper suggest that transport processes associated with the summer monsoons bring increased abundances of hydrochloric acid into contact with liquid sulfate aerosols in the cold tropical lowermost stratosphere, leading to heterogeneous chemical activation of chlorine species. The calculations indicate that the spatial and seasonal distributions of chlorine monoxide and chlorine nitrate near the monsoon regions of the northern hemisphere tropical and subtropical lowermost stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Both satellite and aircraft measurements show that tracer constituents exhibit localized extrema in the upper troposphere lower stratosphere (UTLS) over the Asian and North American monsoon regions during boreal summer, such as maxima of tropospheric species‐like methane (Park et al, ), carbon monoxide (CO; Garny & Randel, ; Li, Jacob, et al, ; Li, Jiang, et al, ; Pan et al, ), and stratospheric water vapor (Dessler & Sherwood, ; Gettelman et al, ; Milz et al, ; Park et al, ; Rosenlof et al, ; Randel et al, , ; Zhang et al, ), and minima of stratospheric species‐like ozone (Gettelman et al, ; Park et al, , ; Randel & Park, ; Randel et al, ). Among these chemical constituents in the UTLS, stratospheric water vapor (SWV) is important due to not only its radiative forcing on surface climate (Forster & Shine, ; Maycock et al, ; Solomon et al, ) but also its chemical effects on stratospheric ozone (Dvortsov & Solomon, ) and chlorine activation reactions (Anderson et al, ; Solomon et al, ). The importance of a realistic representation of the SWV over the Asian summer monsoon region in atmospheric models has been emphasized in simulating troposphere‐stratosphere exchange correctly (Bannister et al, ; Dethof et al, ; Ploeger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both satellite and aircraft measurements show that tracer constituents exhibit localized extrema in the upper troposphere lower stratosphere (UTLS) over the Asian and North American monsoon regions during boreal summer, such as maxima of tropospheric species‐like methane (Park et al, ), carbon monoxide (CO; Garny & Randel, ; Li, Jacob, et al, ; Li, Jiang, et al, ; Pan et al, ), and stratospheric water vapor (Dessler & Sherwood, ; Gettelman et al, ; Milz et al, ; Park et al, ; Rosenlof et al, ; Randel et al, , ; Zhang et al, ), and minima of stratospheric species‐like ozone (Gettelman et al, ; Park et al, , ; Randel & Park, ; Randel et al, ). Among these chemical constituents in the UTLS, stratospheric water vapor (SWV) is important due to not only its radiative forcing on surface climate (Forster & Shine, ; Maycock et al, ; Solomon et al, ) but also its chemical effects on stratospheric ozone (Dvortsov & Solomon, ) and chlorine activation reactions (Anderson et al, ; Solomon et al, ). The importance of a realistic representation of the SWV over the Asian summer monsoon region in atmospheric models has been emphasized in simulating troposphere‐stratosphere exchange correctly (Bannister et al, ; Dethof et al, ; Ploeger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We note that previous multi-model comparisons of the residual circulation that use w * taken directly from models may have been subject to the same issue (e.g. Butchart et al, 2010;SPARC, 2010), though we cannot confirm this. To avoid this methodological inconsistency, Dietmüller et al (2018) recalculated w * from v * using the continuity equation, which requires a vertical integration and a derivative along the meridional direction.…”
Section: Model Namementioning
confidence: 62%
“…Unfortunately, heating rates were not available from all CCMI model simulations to perform the thermodynamic equation calculation. Nevertheless, we compute the direct and downward control principle diagnostics for the residual circulation in a self-consistent manner in the models and reanalyses to enable comparison with earlier multi-model studies (Butchart et al, 2006(Butchart et al, , 2010SPARC, 2010).…”
Section: Downward Control Principle Calculationsmentioning
confidence: 99%
“…to temperatures below 195 K (Kawa et al, 1997). Solomon et al (2016) found chlorine activation on liquid sulfate aerosols near the northern monsoon regions in their model calculations.…”
Section: Clono 2 and Extra-polar Stratospheric Chlorine Chemistrymentioning
confidence: 94%